Rancangan Bangun Sistem Informasi Geografi Menggunakan Google Fusion Tables API Untuk Pengaduan Kerusakan Jalan - Widodo, Wahyu; Nugroho, Wawan Cahyo (Journal of Digital Ecosystem for Natural Sustainability, 2021)
Roads are one of the lifeblood infrastructure of the community in carrying out activities and driving the wheels of the economy through regional development and forming a spatial structure in order to realize national development goals, so that the level of urgency is high. Damage to road infrastructure is one of the contributors to traffic accidents, especially during the rainy season. The relevant government agencies already have information and complaints service units, but there is no system that makes it easier for the public to report road damage that is more specific with maps and location coordinates. Research on the design of a road damage Geographic Information System (GIS) called MySIGSAG to make it easier for the public to report road damage. The results of this study are a web-based and mobile Android GIS program with the name MySIGSAG. Consists of a public panel that contains the home page, splashscreen, and main menus such as reports, map checks, chart checks, and info. In addition, the admin panel contains the main page for managing content. The Relevant government agencies can present comprehensive road damage reports and provide convenience for the public in submitting reports and monitoring the development of road conditions.